Effects of Age on Match-related Acceleration and Deceleration Efforts in Elite Soccer Players - Lorenzo-Martínez, Miguel; Corredoira, Francisco J.; Lago-Peñas, Carlos; Campo, Roberto López-Del; Nevado-Garrosa, Fabio; Rey, Ezequiel (International Journal of Sports Medicine, 2021)
The aim of this study was to examine the effects of chronological age on acceleration and deceleration match performance in professional soccer players. A total of 5317 individual match observations were collected on 420 professional players competing in the Spanish LaLiga during the 2018–2019 season, using a multiple-camera computerised tracking system (TRACAB; ChyronHego, Melville, NY, USA). Players were classified using a k-means cluster analysis into four different age groups: 17–23 years, 24–27 years, 28–30 years, and 31–38 years. Linear mixed models were adjusted to compare the players’ match performance according to their age group and playing position (central defenders, external defenders, central midfielders, external midfielders, and forwards). The results showed that players aged between 31–38 years performed a significantly less total number of accelerations (ES=0.30–0.48) and decelerations (ES=0.29–0.49) in comparison with younger players. These age-related physical performance declines were more pronounced among central defenders, central midfielders, and forwards. However, no significant effects were obtained for players’ maximum acceleration and deceleration capacities. The current findings provide useful information for coaches and strength and conditioning specialists to better understand the effects of age on players’ physical performance and to develop age-tailored training programs.
Keywords: football; match performance; aging; positional roles